Pengaruh Kompetensi 4c Pada Mahasiswa Program Pertukaran Mahasiswa Merdeka (PMM) Terhadap Projek Pembelajaran BIPA - Mira Ulia Tari; Nia Astuti; Muhammad Darwis (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the influence of the 4C competencies on the BIPA learning performance of students participating in the Independent Student Exchange Program (PMM) at Muhammadiyah University Purwokerto. This study employs a quantitative approach using a causal method to determine the cause-and-effect relationship between the 4C competencies and students’ BIPA learning performance. The results indicate that the 4C competencies significantly influence BIPA learning. Additionally, the study found that differences in cultural backgrounds and home universities also affect the learning process experienced by PMM students at Muhammadiyah University Purwokerto.